Determinants of smartphone adoption and its benefits to the financial performance of agricultural households: Evidence from Hoa Binh province, Vietnam - Do, Quan Duc; Nguyen, The Kien; Tran, Tung Thanh; Truong, Thanh Bao; Do, Nga Thi; Hoang, Lam Khanh (Asian Journal of Agriculture and Rural Development, 2023)
Mobile phone usage has come to play a vital role in the enhancement of farmers’ agriculture business. Currently, the adoption of mobile phone technology is considered an important factor in enhancing farmers' access to knowledge of the agricultural market situation. This paper studies the determinants of smartphone adoption in agricultural production and examines the roles smartphone use plays in promoting agricultural firms’ performance. We collected research data from 389 agricultural households in Hoa Binh Province, Vietnam. We considered the impacts of both farmer and farm characteristics on the adoption of smartphones in agriculture. The farmers’ characteristics we examined included the influences of age, education, and gender. For the farm characteristics, we considered the impacts of farm size, farm diversification, and farm location. Using the PLS-SEM method, the results showed that gender had no impact on household smartphone adoption in agricultural production, while education, farm size, farm diversification, and farm location each had a positive effect on smartphone adoption. Farmer age and farm location both impeded smartphone adoption. In addition, as per our expectation, the use of smartphones in agricultural production helped increase the farm’s financial performance. Based on these findings, we offer suggestions to policymakers and researchers in the field of agriculture technologies.